Chess Strategy - Lasker, Edward, 1885-1981; Du Mont, J. (Jules), 1881-1956 (Salt Lake City, UT : Project Gutenberg, 2004)
"Chess Strategy" by Edward Lasker is a comprehensive instructional guide on chess tactics and strategies written in the early 20th century. This book is aimed at players looking to enhance their understanding of chess mechanics and improve their gameplay through structured learning. It covers fundamental concepts about the game, including pieces movement, rules, strategies for openings, middle games, and end-games. The opening portion of the book introduces the basic rules of chess and establishes a clear foundation for understanding the game. Lasker outlines the player$1 (Bs objectives, the positional setup on the board, and how each piece moves according to specific laws, emphasizing the unique characteristics that define their roles. Additionally, he discusses the significance of strategy, encouraging players to cultivate their judgment in evaluating moves rather than simply memorizing techniques. This thorough primer sets the stage for deeper exploration into various strategies and principles that will be discussed in subsequent chapters, aimed at guiding both beginners and more experienced players in their journey through the tactical landscape of chess. (This is an automatically generated summary.)s
Release date is 2004-05-01
John Mamoun, Charles Franks, and the Online Distributed Proofreaders
Keywords: Chess